2017
DOI: 10.1002/hbm.23898
|View full text |Cite
|
Sign up to set email alerts
|

Task‐related changes in degree centrality and local coherence of the posterior cingulate cortex after major cardiac surgery in older adults

Abstract: Objectives: Older adults often display postoperative cognitive decline (POCD) after surgery, yet it is unclear to what extent functional connectivity (FC) alterations may underlie these deficits. We examined for postoperative voxel-wise FC changes in response to increased working memory load demands in cardiac surgery patients and nonsurgical controls.Experimental design: Older cardiac surgery patients (n 5 25) completed a verbal N-back working memory task during MRI scanning and cognitive testing before and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 120 publications
(168 reference statements)
1
24
1
Order By: Relevance
“…These age-related functional changes in brain activation patterns allow for cognitive performance to be preserved (41). When the damaged cognitive preservation was challenged by a cognitive task such as increasing working memory load, the degree centrality and local coherence in the left dorsal posterior cingulate cortex (dPCC) increased, which was inversely associated with global cognitive outcomes (42). It has also been demonstrated that cognitive function such as psychomotor speed would be improved after cerebral arterial perfusion increased (43).…”
Section: Discussionmentioning
confidence: 99%
“…These age-related functional changes in brain activation patterns allow for cognitive performance to be preserved (41). When the damaged cognitive preservation was challenged by a cognitive task such as increasing working memory load, the degree centrality and local coherence in the left dorsal posterior cingulate cortex (dPCC) increased, which was inversely associated with global cognitive outcomes (42). It has also been demonstrated that cognitive function such as psychomotor speed would be improved after cerebral arterial perfusion increased (43).…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic Connectivity Contrast (ICC) was used to determine the magnitude of degree or network centrality by calculating the global strength of connectivity for each voxel with other voxels in the rest of the brain [Martuzzi et al , 2011]. ICC has been frequently applied in recent rsFC studies (Van Ombergen et al , 2017; Vatansever et al , 2017; Walpola et al , 2017; Browndyke et al , 2018; Cassady et al , 2018). It has the advantage of circumventing the need for a priori definitions of regions of interest (Martuzzi et al , 2011).…”
Section: Methodsmentioning
confidence: 99%
“…This approach derived four factor scores that correspond to four cognitive domains: verbal memory; abstraction and visuospatial orientation; visual memory; and attention and concentration. Postoperative cognitive dysfunction was defined as a ≥ 1 standard deviation decrease in one or more of these four cognitive domain from baseline to 6 weeks after surgery as previously described [6,34,35,[37][38][39][40][41][42]. The 6-week time point was selected because it falls within the 1-12month window that POCD/neurocognitive disorder, postoperative occurs, and the 6-week time point has been previously been used extensively in prior studies [6,34,35,[37][38][39][40][41][42].…”
Section: Cognitive Testingmentioning
confidence: 99%